PENERAPAN KONSEP GREEN CHEMISTRY MELALUI KEGIATAN KEBERSIHAN DAN PENGHIJAUAN DI DESA TAMBAK REJO BENGKULU UTARA - Hermansyah Amir; Sura Menda Ginting; Nabila Amalia; Kailia Vanesa Arianti (Universitas Bengkulu, 2025)
These community service activities were conduted at Tambak Rejo Village, Padang Jaya District, North Bengkulu Regency, towards local residences in cooperation with students from Chemistry Education Department, University of Bengkulu, April 27th, 2025. Local residences were very enthusiast with the activities which are socialization of the importance of sustanability act; cleaning activity of waste at local area, and tree restoration as an act of afforestation. These activities are aim to provide green lanscape that can prevent erotion by maintaning the balance between water system and soil strangulation. These act followed the principles of green chemistry concept toward sustainability. Tambak Rejo Village is an areal with vast open field and quite suceptible to draught in dry season. This afforestation project aim to prevent draught, as well as provide green, and beautiful landscape for local residence. These community service activities were done in several steps which are socialization towards local residence, the act of cleaning of local waste, and planting several trees in prepared land. Both local residences and students from Chemistry Education Study Program involved directly in all activities. Keywords: green chemistry, afforestation, sustainability